LEGAL REGULATION SOURCES FOR THE UK CONTRACTUAL RELATIONS - Bocharov, Vyacheslav; Karagodina, Natalia; Zgonnikov, Andrey; Maksimenko, Alexander; Tychinin, Sergey (Revista Inclusiones, 2019)
The presented article discusses the sources of contractual relation legal regulation of private law nature in the United Kingdom of Great Britain and Northern Ireland, based on the peculiarities of their legal system related to the historic Association Agreement. The symbiosis of legislative regulation and judicial precedent is of particular importance to the Great Britain law, which stipulates that it is necessary to rely not only on the norms of law but also on the judicial decisions substantiating their claims